Imaging of the Shoulder With Emphasis on MRI: A Teaching File - Puneet Bhargava; Ramesh Iyer; Sandeep Vaidya (Association of American Medical Colleges, 2010)
Abstract This is an interactive PowerPoint presentation intended to teach radiology, orthopedic surgery, and physical medicine and rehabilitation residents about magnetic resonance imaging (MRI) of the shoulder. At various points in the presentation, the learner is directed via hyperlinks to available online resources that will aid in self-learning. The common patterns of shoulder abnormalities with emphasis on MRI have been illustrated using a case-based approach. This PowerPoint-based resource can be used as a starting point to understand the basic concepts in a simplistic fashion before embarking on more complex imaging of the shoulder. We have used these slides extensively to initiate second-year radiology residents in their initial rotation to MRI of the shoulder. Radiologists with more experience have benefited from this tool by using it for a quick reference and review.